Perbandingan Volume Overburden Berdasarkan Data Survey dengan Data Truck Count pada Pit Section 2 Timur PT. Budi Gema Gempita Kabupaten Lahat, Sumatera Selatan - Rahmi Hasvah; Riko Maiyudi (Departemen Teknik Pertambangan FT UNP, 2021)
PT. Budi Gema Gempita is one of the coal mining companies operating in East Merapi District, Lahat Regency, South Sumatra. The mining system used is an open pit mining system using the Open Pit Mining method. In carrying out mining operations, there are differences in production results from the data recorded by the checker in the form of truck count data and survey data. The results of the calculation of the volume of overburden material based on survey data obtained a comparison of overburden volume based on survey data and truck count data in June 2021 in the East Section 2 pit on the first week 12,574.22 bcm, second week 28,507.03 bcm, third week 16,415.47 bcm and fourth week 53,958.90 bcm.Due to the difference in the volume of survey data with truck count data, in the conclusion with actual condition of the truck count data in the form of overburden material that is sticky on the vessel dump truck or articulated dump truck being transported back to disposal because the type of material transported is in the form of mud (material containing water), making it difficult to stockpile. Meanwhile, by looking at the survey measurement conditions, there is a fill value that has not been transported to disposal, which is measured again in the survey measurement so that it reduces the cut value.